PENTAGON FRAUD ANALYSIS IN DETECTING FRAUDULENT FINANCIAL REPORTING USING F-SCORE MODEL - Titi Purbo Sari; Dian Indriana Tri Lestari (Riset Akuntansi Keuangan, 2020)
This study aims to examine the effect of pentagon fraud on fraudulent financial reporting. The sample used in this study was 144 annual reports on 40 banking companies that were reported on the Indonesia Stock Exchange (IDX) for the period 2015 - 2018. The data analysis method of this study used the method of multiple linear regression analysis. The results showed that the Pressure factor with the Financial Stability category and the Opportunity factor with the Effective Monitoring category had a significant effect on fraudulent financial reporting. Meanwhile, the Pressure factor in the Financial Target and External Pressure categories, Opportunity factor in the Nature of Industry category, Rationalization factor in the Change in Auditor category, Competence factor in the Change In Director category,